Strategi Kepala Madrasah dalam Meningkatkan Kompetensi Guru di MTs Madaniyah Gunung Silanu Kabupaten Jeneponto - Kasmi, Kasmi; Bunyamin, Andi; Syahrul, Muhammad (LP2M Universitas Islam Ahmad Dahlan, 2025)
As a leader, the head of the madrasah has a strategic role in making efforts to develop the quality of madrasah education, especially in the aspect of teacher competency development. In carrying out his role, the head of the madrasah must identify the needs of teacher competency development by making a development plan that is in accordance with the needs of teachers and the madrasah in order to create optimal improvements. This study aims to determine the efforts of the head of the madrasah in improving teacher competency and to reveal the effectiveness of efforts on teacher competency at MTs Madaniyah Gunung Silanu. This study uses a qualitative approach with a case study type. The data collection techniques used are observation, interview and documentation techniques. Data analysis is carried out by data reduction, data presentation and drawing conclusions. The results of the study indicate that the efforts made by the head of the madrasah in improving teacher competency at MTs Madaniyah Gunung Silanu are creating training programs, involving teachers in MGMP activities, supervising and providing motivation. The effectiveness of some of these efforts is improving teachers' abilities in designing learning, developing teachers' mastery of teaching materials, training teachers' social skills and improving teacher discipline.